2017
DOI: 10.1080/1354750x.2017.1360943
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical alterations induced by nickel oxide nanoparticles in female Wistar albino rats after acute oral exposure

Abstract: This study revealed that exposure to nanosized NiO particles at acute doses may cause adverse changes in animal biochemical profiles. Further, the in vivo studies on toxicity evaluation help in biomonitoring of the potential contaminants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
33
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 44 publications
(44 citation statements)
references
References 63 publications
11
33
0
Order By: Relevance
“…Similar findings were also reported in a study conducted on MgO-NPs by Mangalampalli et al (2017). A similar type of increased liver, serum enzyme activities and decreased kidney enzyme actvities was observed in an acute study with NiO-NPs administartion (Dumala, Mangalampalli, Kalyan Kamal, & Grover, 2018). Sarkar, Ghosh and Sil (2014) observed that NPs had produced ROS to a more prominent degree bringing about expanded proinflammatory reactions and oxidative stress through intracellular signaling pathways.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Similar findings were also reported in a study conducted on MgO-NPs by Mangalampalli et al (2017). A similar type of increased liver, serum enzyme activities and decreased kidney enzyme actvities was observed in an acute study with NiO-NPs administartion (Dumala, Mangalampalli, Kalyan Kamal, & Grover, 2018). Sarkar, Ghosh and Sil (2014) observed that NPs had produced ROS to a more prominent degree bringing about expanded proinflammatory reactions and oxidative stress through intracellular signaling pathways.…”
Section: Discussionsupporting
confidence: 81%
“…Similar findings were also reported in a study conducted on MgO‐NPs by Mangalampalli et al (). A similar type of increased liver, serum enzyme activities and decreased kidney enzyme actvities was observed in an acute study with NiO‐NPs administartion (Dumala, Mangalampalli, Kalyan Kamal, & Grover, ).…”
Section: Discussionsupporting
confidence: 70%
“…Furthermore, reports have shown the ability of NiO‐NPs to induce genotoxicity and substantial physicochemical perturbation on Allium cepa , which confirmed that these NPs are hazardous to the environment (Manna & Bandyopadhyay, , ). NiO‐NPs were shown to cause biochemical alterations (Dumala, Mangalampalli, Kalyan Kamal, & Grover, ) and genotoxicity in Wistar rats when exposed to acute doses via an oral route (Dumala et al, ). Moreover, there is evidence of induced cell death and cytogenetic anomalies in rats exposed orally for 14 days to NiO‐NPs.…”
Section: Introductionmentioning
confidence: 99%
“…Although Ni and its compounds were classified as class 1 carcinogens (IARC, ), increase in the use of NiO NPs makes it necessary to have a clear understanding of their probable effect on the health of humans and the environment. Acute oral dose toxicity study of NiO NPs on Wistar rats showed significant genotoxicity and biochemical alterations (Dumala et al, ; Dumala, Mangalampalli, Kalyan Kamal, & Grover, ). NiO NPs when ingested through oral route for 14 days, induced genotoxicity and enzymatic imbalance that triggered apoptosis in male Wistar rats.…”
Section: Introductionmentioning
confidence: 99%